Evolusi Sistem Operasi Android: Sebuah Tinjauan Literatur - Raditya, Maulana Krisna (Universitas Pelita Bangsa, 2023)
In the past, mobile phones were only used to make calls, but with the introduction of smartphones, mobile phones have evolved into low-power handheld processing systems. This evolution is due to the operating system for mobile phones that make them sophisticated and have their own processing and storage. Today mobile phones provide many functions from making calls to sending messages, multimedia sharing, email, socializing applications, word processing, excel worksheets to various multiplayer games and much more. The operating systems for these handheld devices are iOS from Apple Inc, Windows from Windows Inc and Android from Google. Among competitors in the smartphone operating system industry, Android holds the largest market share in terms of units shipped worldwide and number of users. Android is an open source operating system based on the linux kernel where applications run on an application framework that controls activities supported by Dalvik libraries and virtual machines that compile and convert all java class files into a single file. There are several virtual machines running simultaneously on a single device that run different applications or application instances. The Android operating system provides memory management, process management to run applications and services. Every android release improves the user experience and brings enhanced features. This paper presents a study of the evolution that each release brings to the android operating system.